2015
DOI: 10.1002/mus.24570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and hand dominance on size of the lower trapezius muscle

Abstract: Gender and side dominance differences should be controlled for when investigating lower trapezius muscle thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Consistent with a previous study, thickness of the lower trapezius muscle was greater on the right (dominant) side than the left (nondominant) side in the healthy controls, which supports a side dominant difference in thickness of the lower trapezius muscle. However, in contrast to healthy controls, the results demonstrated no side difference in thickness of the lower trapezius muscle in individuals with chronic neck pain.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with a previous study, thickness of the lower trapezius muscle was greater on the right (dominant) side than the left (nondominant) side in the healthy controls, which supports a side dominant difference in thickness of the lower trapezius muscle. However, in contrast to healthy controls, the results demonstrated no side difference in thickness of the lower trapezius muscle in individuals with chronic neck pain.…”
Section: Discussionsupporting
confidence: 90%
“…The ultrasound procedures were performed according to a previous study . Participants were positioned prone on a treatment plinth with the head in midline, the arms to the side and the palms facing up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, this work may be the first study to evaluate potential factors affecting UT elasticity with SWE, including gender, age, UT thickness and BMI. No previous studies have analyzed so many factors on muscle elasticity as we did 36,37 . Thirdly and most important, the clinical significance of this study lies in providing quantitative baseline measurements for UT muscle strain through determining the reference ranges of normal UT elasticity during different shoulder abduction with SWE.…”
Section: Discussionmentioning
confidence: 93%
“…The high utilization of the dominant versus the nondominant side may contribute to the long-term usage of the extensor muscles, which reasonably explains the differences in stiffness. Uthaikhup et al [30] examined the thickness of the lower trapezius and found greater lower trapezius muscle thickness on the dominant versus the nondominant side of 0.43 ± 0.02 mm. Fatigue of the upper trapezius also differed bilaterally; the upper trapezius on the dominant side was less fatigable by surface EMG [31].…”
Section: Discussionmentioning
confidence: 99%